Neuroprotective Effect of Fagopyrum dibotrys Extract against Alzheimer's Disease. (20th April 2017) - Liang, Chen; Yuan, Jian-Ping; Ding, Tao; Yan, Lv; Ling, Lu; Zhou, Xin-Fu; Zeng, Yue-Qin
Abstract : Accumulated evidence suggests that polyphenolic antioxidants present in herbs play important roles in prevention of AD; the molecular mechanisms behind neuroprotective actions rely on the phenols through different effects on the amyloid-aggregation pathway. Fagopyrum dibotrys is a traditional herbal medicine which contains high quantity phenols. In present study, we investigate the beneficial pharmacological actions of Fagopyrum dibotrys extract in the APP/PS1 transgenic mouse mode; meanwhile, effects of the FDE on the fibrillation and cytotoxicity of A β peptide were evaluated in vitro. After 9-month treatment, FDE exhibited multifunctional properties on A β -related pathologies, which cleaned A β deposits in the brain and decreased A β burden in the plasma, inhibited microhaemorrhage, and reduced reactive microglia in APP/PS1 transgenic mice and also promoted A β fibrils disaggregation and inhibited neurotoxicity induced by A β in SH-SY5Y cells. These results highlighted that FDE is an AD type pathology modulator with therapeutic potential against AD.